INSTITUTIONAL ECONOMICS RELEVANT TO ISLAMIC FINANCE - Abdul Ghafar Ismail (Sharia and Law Faculty, 2017)
The study on the relevancy of institutional economics to mainstream Islamic economics especially in Islamic finance is not widely known. The relevancy issue arises due to: the role of revelation and reason; and the assumption of an ideal Islamic financial institutions; the role of both institutional environment and institutional arrangements on the setting-up of the Islamic financial institutions. Thus, the discussion in this paper provides a brief (and admittedly unbalanced) sketch of the new institutional economics which is relevant to Islamic finance. The literature in NIE is expanding rapidly and gaining increasing adherents and influence in Islamic finance. Our findings show that it is a highly diverse field and its many branches are rich in theoretical insight, relevant for policy and empirically useful.